Persistence and change in rural communities : a 50-year follow-up to six classic studies (CABI, 2002)
A reexamination of the six rural community study areas in the USA is presented to document some of the diverse patterns of social organization and change that have characterized US rural communities over the 50 years following the original study effort. It also discusses the community characteristics that persisted. The book consists of 9 chapters. Chapter 1 provides the introduction. Chapter 2 presents an overview of major theoretical perspectives that provide a foundation for addressing these issues. Chapters 3-8, which present individual case study reports for each of the 6 communities, provide an examination of contemporary community conditions as juxtaposed against the conditions ensued since that time. Chapter 9 draws upon the findings from all 6 of the case study chapters in: developing a comparative assessment of the patterns of change that have occurred; the effects of change on community capacity and localized social interaction processes; and the implications of such changes for rural community well being and rural development policy. An index is provided.